Bom Atom di Atas Hiroshima) Suatu Pengalaman Nyata - Arifin Bey, Arifin Bey (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1989)
The author was one of the students from occupied territories in South East Asia studying in Hiroshima when the city was atomic bombed in 1945. Tokyo was carpet-bombed in 1944-45 and foreign students were spread to other relatively safe cities. Before August 1945 Hiroshima was never bombed, but air raid alarms sounded every morning. On August 6 after the alarm was cleared the author saw a